AN ANALYSIS OF THE USE OF AUXILIARY VERB TA- BAKARI - Mariam Toliwongi (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
One sentence pattern in Japanese which means the same or synonym in Indonesian are ta tokoro da and ta bakari da which means